2017
DOI: 10.1007/978-981-10-4307-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidences Supporting the Benefits of Exercise Training in Heart Failure

Abstract: Heart Failure (HF), a common end point for many cardiovascular diseases, is a syndrome with a very poor prognosis. Although clinical trials in HF have achieved important outcomes in reducing mortality, little is known about functional mechanisms conditioning health improvement in HF patients. In parallel with clinical studies, basic science has been providing important discoveries to understand the mechanisms underlying the pathophysiology of HF, as well as to identify potential targets for the treatment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 180 publications
0
2
0
Order By: Relevance
“…It was shown that several preclinical studies have already provided molecular insights for the beneficial effect of exercise in various induced HF animal models. As a whole, exercise training can ameliorate HF-induced dysfunctions by acting on the current standard pharmacological care-targeted pathways (16,17) or non-pharmacological available targets correcting the inflammatory response, skeletal myopathy, and vagal outflow (16,17). More recently, exercise was demonstrated to activate cardio-myogenesis in adult mice and the robust cardiomyogenic response was also observed in the adjacent area of the infarcted zone (18).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that several preclinical studies have already provided molecular insights for the beneficial effect of exercise in various induced HF animal models. As a whole, exercise training can ameliorate HF-induced dysfunctions by acting on the current standard pharmacological care-targeted pathways (16,17) or non-pharmacological available targets correcting the inflammatory response, skeletal myopathy, and vagal outflow (16,17). More recently, exercise was demonstrated to activate cardio-myogenesis in adult mice and the robust cardiomyogenic response was also observed in the adjacent area of the infarcted zone (18).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of clinical and experimental data have confirmed that physical exercise can reduce the occurrence and development of chronic HF through its natural and powerful inflammatory inhibition, but its molecular mechanism for inhibiting inflammatory response is still inconclusive. [7][8][9] Existing evidence shows that exercise can effectively reduce the levels of inflammatory factors IL (interleukin)-1β, TNF-α (tumor necrosis factor-α), CRP (C-reaction protein) in the serum of patients with coronary heart disease, and effectively increase the content of anti-inflammatory factors IL-10, IL-1ra, and other cytokines. 10 Correspondingly, in the absence of exercise intervention, the treatment of HF with the IL-1 receptor antagonist-anakinra can effectively improve the exercise tolerance of patients.…”
mentioning
confidence: 99%